Edukasi Produk Halal untuk Meningkatkan Pengetahuan dan Pemahaman Pelaku UMKM Cilor Sekitar Palima Kota Serang - Devina Lestia Utami; Azuza Evania; Alya Rahma Zahratunnisa; Fadilah Ramadani; Depi Herawati; Riski Andrian Jasmi (Universitas Teuku Umar, 2025)
The low level of awareness and understanding among micro, small, and medium enterprises (MSME) regarding the concept of product halalness remains one of the main obstacles in strengthening the halal industry in Indonesia. Many business owners still lack knowledge about the importance of halal certification and the proper ways to ensure the halal integrity of ingredients and production processes. This activity aimed to improve the knowledge and understanding of Cilor MSME entrepreneurs around Palima, Serang City, regarding the concept of halal products through halal education activities. The methods used included interviews, interactive counseling sessions, and evaluations through pretest and posttest assessments. The activity was carried out in several locations around Palima, involving multiple business owners as participants. The results indicated a significant improvement in participants’ understanding, where the average pretest scores ranged from 30–65%, while posttest scores increased up to 100% in most indicators. These findings demonstrate that halal education activities are effective in enhancing halal literacy and increasing MSME awareness of the implementation of halal principles in production.